A phase I trial of talazoparib and irinotecan with and without temozolomide in children and young adults with recurrent or refractory solid malignancies. (September 2020) - Federico, Sara M.; Pappo, Alberto S.; Sahr, Natasha; Sykes, April; Campagne, Olivia; Stewart, Clinton F.; Clay, Michael R.; Bahrami, Armita; McCarville, Mary B.; Kaste, Sue C.; Santana, Victor M.; Helmig, Sara; et al.
Abstract: Background: Talazoparib combined with irinotecan and temozolomide demonstrated efficacy in a murine Ewing sarcoma model. Based on these data, we conducted a phase I trial of talazoparib and irinotecan with/without temozolomide in paediatric patients with recurrent/refractory solid malignancies. Patients and methods: Cohorts of 3–6 patients with recurrent/refractory solid malignancies received escalating doses of oral talazoparib and intravenous irinotecan (arm A) and oral talazoparib, oral temozolomide and intravenous irinotecan (arm B) in a 3 + 3 design. Talazoparib was administered on days 1–6, and intravenous irinotecan and oral temozolomide were administered on days 2–6, of a 21-day course. Serum for talazoparib and irinotecan pharmacokinetics was obtained during course 1. UGT1A1 polymorphism and Schlafen family member 11 (SLFN11) immunohistochemical staining were performed. Results: Forty-one patients (20 males; median age, 14.6 years; 24 with recurrent disease) were evaluable for dose escalation. Twenty-nine and 12 patients were treated on arm A and arm B, respectively, for a total of 208 courses. The most common diagnosis was Ewing sarcoma (53%). The most common ≥grade III haematologic toxicities in arms A and B included neutropenia (78% and 31%, respectively) and thrombocytopenia (42% and 31%, respectively). In arms A and B, febrile neutropenia (24% and 14%, respectively) and diarrhoea (21% and 7%, respectively) were the most common ≥grade III non-hematologic toxicities. Six patients (Ewing sarcoma [5 patients] and synovial sarcoma [1 patient]) had a response (1 with a complete response, 5 with a partial response). The objective response rates were 10.3% (arm A) and 25% (arm B). Pharmacokinetic testing demonstrated no evidence of drug-drug interaction between talazoparib and irinotecan. UGT1A1 was not related to response. SLFN11 positivity was associated with best response to therapy. Conclusions: The combination of talazoparib and irinotecan with/without temozolomide is feasible and active in Ewing sarcoma, and further investigation is warranted. Highlights: Talazoparib with irinotecan and temozolomide is tolerated in paediatric patients. There was no drug-drug interaction between talazoparib and irinotecan. UGT1A1 status was significantly associated with a course 1 dose-limiting toxicity. Schlafen family member 11 positivity was associated with best response to therapy. This regimen had clinical benefit in patients with Ewing sarcoma.